Application of the Finland Education Model at the Daaru Tahfiz Islamic Boarding School in Shaping the Quality and Character of Santri - Nur, Muhammad; Sesmiarni, Zulfani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
Education brings changes to a better standard of living, has an impact on the level of human welfare and happiness. So it would be very naïve, when education is not made a priority in life there will be inequality and all things, stagnation in thinking and weakness of human morality which leads to the occurrence of various kinds of pathologies that disturb humanity and undermine civilization. Finnish education seems to be an inspiration for better education with all its models and strategies, which have succeeded in making Finland the country with the best level of education in the world. The Daaru Tahfiz Islamic Boarding School in the Agam Regency of West Sumatra initiated the application of this educational model in existing activities, so as to achieve better results in improving the quality and character of the students.